Developing theory on sustainable integration of GenAI in tertiary English language teaching: The triadic GenAI integration theory - Gendolf Niepes (Universitas Negeri Semarang, 2025)
Artificial Intelligence (AI) revolutionizes tertiary language education with innovations, cautions, and questions. It also raises significant ethical and pedagogical concerns that impact both educators and future professionals. This led to a decline in future professionals' critical thinking, creativity, and values. This study aims to develop a strategic framework that would describe the sustainable integration of GenAI in tertiary English language teaching. A deductive approach to theory development was utilized, where scholarly literature is the foundation for generating a theory. Secondary analysis was used to analyze the data collected from research studies and literature. The theory was developed based on the readings and discussion of the process of integrating GenAI into tertiary language education. Axioms were generated to come up with propositions. The following propositions are posed: 1) GenAI integration should be aligned with language proficiency; 2) The development of language skills should be alongside AI literacy; 3) core educational values and sustainability principles should guide GenAI integration. The propositions concluded that the strategic approach for sustainably integrating GenAI in tertiary English language education has three key elements: aligning AI tools with language proficiency levels, embedding AI literacy within the higher education curriculum, and ensuring implementation is guided by educational values and long-term sustainability. This framework, known as the Triadic GenAI Integration Theory, aims to guide teachers in effectively incorporating GenAI into their teaching practices while focusing on language learning objectives and ethical considerations of future professionals.